The world's religions - Huston Smith (HarperCollins, 1991)
The book presents with details the world's religions: Hinduism, Buddhism, Confucianism, Taoism, Islam, Judaism, and Christianity. It features expanded sections on the inner dimensions of these great religious traditions, with fresh emphasis on Tibetan Buddhism, Sufism, and the teaching of Jesus. Included here also is a chapter on the pirimal religion - the symbolically rich native traditions of the Americas, Australia, Africa, and Oceania. This book is a thoroughly researched, informative, and fascinating presentation of both the differences and similarities in world-wide religious traditions